Capital Flight and its Determinants: The Case of Ethiopia1 . (14th June 2016) - Geda, Alemayehu; Yimer, Addis
Abstract: This study attempts to estimate the volume of capital flight from Ethiopia and its determinants, focusing on economic, institutional, and political determinants. Capital flight is estimated at $31 billion over the 1970–2012 period. On average, the country has lost around half a billion dollars annually under the 'Derg' regime. This amount more than doubled to over 1 billion per annum during the EPRDF regime. The empirical evidence suggests that macroeconomic instability, the degree of financial market deepening, exports, interest rate differentials, political instability, corruption, and debt‐creating flows are the most important determinants of capital flight from Ethiopia. The political environment is also found to be crucial. Generally, capital flight was high before violent regime changes and low in the subsequent periods, when regimes were in the process of establishing a firmer grip on power; after this point, however, capital flight began to rise significantly again. The historical analysis points to potential causality running from political factors to capital flight. A strong improvement in economic and political governance will be key to abating the problems of capital flight in Ethiopia.